Amygdala-Prefrontal Oscillatory States Govern the Retrieval of Fear and Extinction Memories - Ozawa, Minagi. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Neuroscience.; Advisor: Leon Reijmers.; Committee: Michele Jacob, Dong Kong, and Mimi Kao.; Keyword: Neurosciences.; Memories of fearful experiences can be adaptively controlled by extinction learning. The behavioral expression of both learned fear and safety is associated with distinct oscillatory activity in the basolateral amygdala (BLA) and medial prefrontal cortex (mPFC). However, if and how these oscillatory network states support the retrieval of fear and extinction memories remains elusive. To investigate this, we subjected mice to contextual fear conditioning and extinction, and used rhythmic optogenetic manipulation to mimic endogenous oscillatory patterns across various memory states. This enabled us to probe learning-induced changes in the BLA-mPFC network structure, and test for oscillatory contributions to memory retrieval. We found that exogenously induced 4Hz and 8Hz oscillatory activity in the BLA increased and decreased conditioned freezing behavior, respectively, consistent with their endogenous behavioral associations. This bidirectional behavioral control was only observed after extinction learning and selectively in the conditioned context, indicating critical roles for these two oscillations in the retrieval of opposing fear and extinction memories. Within the BLA, exogenously induced 4Hz and 8Hz oscillatory activity had an experience-dependent ability to synchronize local neuronal activity to the stimulation frequency, and recruit distinct functional neuronal ensembles in a memory-state specific manner. At the network level, we observed experience-dependent oscillatory interactions between the BLA and mPFC, which we demonstrate, via simultaneous manipulation of BLA and mPFC, can support post-extinction fear memory retrieval. Our findings uncover experience-dependent changes in local and interregional theta-range resonance properties of BLA-mPFC circuits that support the retrieval of fear and extinction memories, and suggest novel approaches for interrogation and therapeutic manipulation of acquired fear circuitry.